Family Tax Relief in Poland in Comparision to Selected Countries - Wiśniewska-Kuźma, Magda (Studia Oeconomica Posnaniensia, 2018)
As a response to today's demographic problems, which have adverse effects on the public finance system, a number of measures are being taken as part of a pro-family policy. The fiscal policy tools are its key element, such as direct benefits from the state budget and public expenditures carried out with the use of special tax structures (so-called tax expenditures), which include a family tax relief for personal income tax, operating in Poland since 2007. It has undergone numerous changes aimed at strengthening its redistributive character and supporting low-income taxpayers. This paper reviews the key changes in the construction of relief over years. The author has set out a research goal to estimate the level of savings in income tax due to family tax relief and their importance in the budget of the household receiving income in the amount of the average wage in the economy and presenting it in comparison with other countries representing different economic models and thus applying different principles of pro-family and fiscal policies. The research hypothesis assumes a relatively high significance of savings for family tax relief in Polish households compared to other countries using this type of support, despite the lower amount of relief from the central value in the surveyed group. The verification was carried out using comparative analysis of indicators developed by the author.